2022
DOI: 10.3390/biomedicines10010177
|View full text |Cite
|
Sign up to set email alerts
|

Detection Rate and Clinical Impact of PET/CT with 18F-FACBC in Patients with Biochemical Recurrence of Prostate Cancer: A Retrospective Bicentric Study

Abstract: Our aim was to assess the detection rate (DR) of positron emission computed tomography (PET/CT) with anti-1-amino-3-[18F]-flurocyclobutane-1-carboxylic acid (18F-FACBC) in patients with biochemical recurrence (BCR) from prostate cancer (PC). As a secondary endpoint, we evaluated 18F-FACBC PET/CT’s impact on patients management. Clinical records of 81 patients submitted to 18F-FACBC PET/CT due to PC BCR in two Italian Nuclear Medicine Units were retrospectively assessed. DR was gauged in the whole cohort and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…These data were also recently confirmed in the retrospective study by Filippi et al, recording a promising performance for low PSA values (DR of 66.7% for PSA <0.57 ng/mL and of 71.4% for PSA 0.57–0.99 ng/mL). In addition, the authors identified 1.1 ng/mL as the optimal cut-off value in predicting a positive PET/CT scan [ 25 ]. The minimal PSA threshold to improve the [ 18 F]fluciclovine PET/CT DR in BCR PCa patients was already investigated by Armstrong et al, who suggested a PSA cut-off of 2.10 ng/mL [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These data were also recently confirmed in the retrospective study by Filippi et al, recording a promising performance for low PSA values (DR of 66.7% for PSA <0.57 ng/mL and of 71.4% for PSA 0.57–0.99 ng/mL). In addition, the authors identified 1.1 ng/mL as the optimal cut-off value in predicting a positive PET/CT scan [ 25 ]. The minimal PSA threshold to improve the [ 18 F]fluciclovine PET/CT DR in BCR PCa patients was already investigated by Armstrong et al, who suggested a PSA cut-off of 2.10 ng/mL [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic performance of [ 18 F]FACBC was widely assessed after the FDA’s approval. The reported overall detection rate for [ 18 F]FACBC ranged from 40% to 80%, depending on the size of patient cohorts, and like [ 11 C]choline, its detection rate positively correlated with patients’ PSA levels(see Table 2 [ 37 , 38 , 39 , 40 , 41 , 42 , 43 ]). In a study investigating BCR patients with very low PSA levels (≤0.3 ng/mL), the detection rates were 43.8% for patients with PSA level below 0.1 ng/mL, increasing up to 65.2% for patients with PSA between 0.2 and 0.3 ng/mL [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…18 F-fluciclovine PET is feasible for patients with PSA <1.0ng/ml. Filippi et al ( 54 ) found that the detection rate in 81 Italian patients was 66.7% when the PSA level was 0.2-0.57 ng/ml, and Wang et al. ( 75 ) in 46 patients with PSA level of 0.3-1.0ng/ml found the positive rate was about 33%, but it was not found positive cases in very low PSA (less than 0.3ng/ml) BCR patients.…”
Section: Pet Imaging For Bcr Of Low Psa Levelsmentioning
confidence: 98%